Regional Urban Planning as a Tool to Combat Climate Change : The Case of Passo Fundo-RS - Ickert, Carina; Pissolatto Neta , Antinesca Joana; Silva, Thaísa Leal da (Scientific Journal ANAP, 2025)
Objective – This study aims to analyze the measures adopted by the public administration of Passo Fundo-RS to make urban planning more resilient in areas such as urban mobility and the environment, in order to improve responses to climate change.Methodology Literature review on the themes of urban planning, mobility, and urban resilience; document analysis; collection of urban indicators; and analysis and discussion of results.Originality/Relevance – The relevance of this research lies in its investigation of urban mobility and environmental policies and indicators, as well as public instruments being developed to make the city of Passo Fundo-RS more resilient in the face of increasingly frequent extreme climate events.Results It was found that the city of Passo Fundo-RS has a Master Plan, Mobility Plan, Goals Plan for Passo Fundo Management 2021-2024 and, recently, a Contingency Plan was created for the Civil Defense area. According to the Report of the Goals Plan for Passo Fundo Management 2021-2024, of a total of twelve goals established for the areas of Urban Mobility and Environment, nine were fully achieved and only three remain in development, resulting in the fulfillment of 75% of the goals proposed in the Goals PlanTheoretical/Methodological Contributions – This study contributed to the understanding that investigations and studies involving the collection and analysis of urban indicators can support decision-making by public authorities, as well as the development of public policies grounded in scientific data.Social and Environmental Contributions – From a social and environmental perspective, it was found that the political and environmental education of citizens and their leaders can contribute to building a more resilient city.
Keywords: Urban Planning; Climate Change; Governance; Urban Mobility